L’interopérabilité culturelle et l’interculturalité - Reine Al Sahyouni Bou Fadel (Communication)
The author presents an example of interoperability centred around cultural dimensions marked by cultural differences and cultural openness. Within this intercultural world where information and communications technology is now a significant evolutionary factor integrated with knowledge sharing, interoperability and cooperation underpin our ability to collaboratively mobilize, understand the value of cultural diversity, ensure the interoperability of systems and internal and external norms, and establish an effective and lasting framework for sharing good practices.